STUDY THE STRUCTURE OF STUDENTS’ MOTIVATION AT MEDICAL UNIVERSITY - Коваленко, І.М.; Осипенко, І.П. (World of Medicine and Biology, 2014)
Presented are the analysis results of students’ motivation, study years 2 – 5, at National Pirogov Memorial Medical University, Vinnytsya. Studies show the most important motivation points are assurance of future career success, opportunity to become highly skilled specialist with deep and solid understanding of future profession. Results received demonstrate clear understanding of the essence of the future career and the need to obtain wide range of skills and excellent knowledge.